Exposure to Persistently Delinquent Peers and Substance Use Onset: a Test of Moffitt's Social Mimicry Hypothesis - Widdowson, Alex O. (Crime & delinquency, 2020)
Moffitt's social mimicry hypothesis states that the sudden rise in offending during adolescence is partly the result of adolescence-limited delinquents modeling the behavior of their life-course persistent peers. We test this hypothesis using social network data from 7,742 adolescents followed from 6th to 12th grades to consider whether having a persistently delinquent friend, especially one who used substances, predicted substance use initiation. Results indicated that although having a persistently delinquent friend was associated with an increased risk of general substance use initiation, adolescents who had a persistently delinquent friend were just as likely to initiate smoking, drinking, and marijuana use whether that friend used that specific substance or not, which suggests that adolescents may not mimic their friends' use of specific substances.